Uso de pré-tratamentos e hidrólise subcrítica de biomassas residuais de laranja para obtenção de açúcares redutores fermentescíveis - Azevedo, Amanda Rampelotto de (2023)
Clean extraction technologies are emerging, viable and promising processes for use in biorefineries. This approach refers to the conversion of lignocellulosic waste biomass into compounds with greater added value. Orange (Citrus sinensis) is a product of great agricultural importance, generating by-products with bioactive properties that can be applied in different sectors, such as food, pharmaceutical and cosmetics. Therefore, the present study aims to evaluate the hydrolysis process with subcritical water of orange by-products (peel and pomace) to obtain reducers sugars. Firstly, the fresh orange peels and pomace were obtained, identified and characterized. Subsequently, the orange biomasses were separated and classified into three types: untreated biomasses; biomasses pre-treated with Soxhlet; and biomass pre-treated with supercritical CO2. For Soxhlet, 250 mL of n-hexane were used in a reflux time of 6 hours. For supercritical CO2, the system conditions were: pressure of 25 MPa, flow of 3 mL/min and total extraction time of 60 min. Finally, hydrolysis tests were conducted with subcritical water. The experimental conditions investigated were varying the process temperature at 180, 200 and 220 °C, for pressures of 15, 20 and 25 MPa. The total hydrolysis reaction time was 60 min with a solvent flow rate set at 10 mL/min. The highest yields of reducers sugars were 5.31 and 4.26 g/100 g of biomass under Soxhlet conditions - Shell at a temperature of 180 ºC and pressure of 15 MPa and Soxhlet-Bagasse at a temperature of 200 ºC and pressure of 20 MPa. Analysis of the hydrolyzed solutions by high-performance liquid chromatography (HPLC) showed the presence of xylose, glucose, arabinose, cellobiose, 5-hydroxymethylfurfural (HMF), furfural and organic acids (acetic, levulinic and formic). Xylose was the predominant monosaccharide in orange hydrolysates, resulting in 21.12 and 24.45 g/L under supercritical CO2 conditions - Peel at a temperature of 180 ºC and pressure of 15 MPa and Without Treatment - Bagasse at a temperature of 220 ºC and pressure of 25 MPa. It is concluded that the orange by-products used in the tests were fully utilized, and that using subcritical technology it was possible to obtain sugars C5 (xylose and arabinose), C6 (glucose) and glycosyl-glucose disaccharide (cellobiose) from the peels and pomace of orange.